Transfer Of Billing Rights To Third Parties In The Banking System - Sitompul, Ariman (Universitas Dharmawangsa, 2023)
In the banking world, the implementation of Cessie is generally due to Old creditors requiring financing so that the operational implementation of their business continues to run. In the provision of bank credit should be made in a written form, and the bank must have confidence in the ability and ability of the debtor customer obtained from the results of both internal and external assessments , capabilities, both capital,as well as collateral and business prospects of the debtor customer. The implementation of cessie according to Article 613 of the Civil Code is carried out on receivables on behalf of the old creditor, to the new creditor on the debt of the debtor by making a cessie deed, either an authentic deed or a deed under the hand with the obligation to be notified to the debtor or in writing approved and recognized by the debtor. With legal consequences receivables switch from the old creditor to the new creditor.